Gentrification: The Complexity of the Process and the Ambiguity of the Phenomenon. A Review of a Book by Łukasz Drozda: Uszlachetniając przestrzeń. Jak działa gentryfikacja i jak się ją mierzy - Zwęglińska, Dominika (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2017)
Gentrification: The Complexity of the Process and the Ambiguity of the Phenomenon. A Review of a Book by Łukasz Drozda: Uszlachetniając przestrzeń. Jak działa gentryfikacja i jak się ją mierzy.